Estrogen‐related receptor participates in regulating glycolysis and influences embryonic development in silkworm Bombyx mori. Issue 2 (22nd October 2019) - Long, W.; Wu, J.; Shen, G.; Zhang, H.; Liu, H.; Xu, Y.; Gu, J.; Jia, L.; Lin, Y.; Xia, Q.
Abstract: Estrogen‐related receptors (ERRs) play indispensable roles in development, energy metabolism, and cancers and are metabolic switches in Drosophila . However, the mechanism underlying their metabolic role is unknown in insects. This study analysed the expression profiles of Bombyx mori ERR ( BmERR ), hexokinase ( BmHK ), pyruvate kinase ( BmPK ) and phosphofructokinase ( BmPFK ) during embryonic development. The expression of BmERR tended to be similar to that of the other genes. We observed a regulatory association between BmERR and glycolytic rate‐limiting enzymes by BmERR overexpression, RNA interference (RNAi), and ERR inhibitors in B. mori embryo cells. Subsequently, ERR cis‐regulation elements (ERREs) were predicted and identified in the BmPFK promoter. Transfection assays, electrophoretic mobility shift assays and chromatin immunoprecipitation showed that BmERR can bind to one of these elements to regulate the expression of BmPFK . ERREs were also predicted in the BmHK and BmPK promoters. In the eggs, the expression of glycolytic rate‐limiting enzyme genes was suppressed when the expression of BmERR was interference by double‐stranded BmERR, the glucose levels also was increased. Meanwhile, the development of silkworm embryos was delayed by about 1 day. These results indicate that BmERR can bind to the ERREs of glycolytic gene promoters and regulate the expression of glycolytic genes, ultimately affecting embryonic development in silkworms. Abstract : Bombyx mori estrogen‐related receptor (BmERR) can affect embryonic development through participating in glycolysis in silkworms. BmERR affects glycolysis by up‐regulating the expression of B. mori phosphofructokinase ( BmPFK ). BmERR binds to the ERRE motif in the BmPFK promoter to regulate the expression of BmPFK .